Methodology for the evaluation of environmental costs in thermal generation in Peru - Rojas Romero, Karin Corina (2022)
Evaluating the costs of electricity generation is important to be able to estimate the variable costs, characterized by the maintenance costs of the generation, transmission and distribution systems. In this work we evaluate the plants that use Camisea natural gas, which is an alternative to the plants that use fossil fuels, not only in terms of costs, but also in terms of the levels of contamination that they cause. The method presented can be taken as a reference for other evaluation mechanisms with similar characteristics.